2017
DOI: 10.3389/fimmu.2017.00266
|View full text |Cite
|
Sign up to set email alerts
|

Specific Strains of Lactic Acid Bacteria Differentially Modulate the Profile of Adipokines In Vitro

Abstract: Obesity induces local/systemic inflammation accompanied by increases in macrophage infiltration into adipose tissue and production of inflammatory cytokines, chemokines, and hormones. Previous studies have shown that probiotics could improve the intestinal dysbiosis induced by metabolic diseases such as obesity, diabetes, and metabolic syndrome. Microorganisms could (directly or indirectly) affect adipokine levels due to their capacity to induce translocation of several intestinal microbial antigens into syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 84 publications
4
41
1
Order By: Relevance
“…Previous observations have suggested that endotoxins from non-commensal bacteria may affect adipocytokine levels secondary to translocation induction of several intestinal microbial antigens into the circulation, creating an altered adipokine profile and intestinal dysbiosis [34]. Certain probiotics, specifically lactic acid bacteria strains, have demonstrated in vitro that they can differentially modulate adipokine expression and the inflammatory response [35]. It is noteworthy that 6 of the 8 probiotic strains used in this study belong to the lactic acid bacteria class.…”
Section: S Sabico Et Al / Clinical Nutrition 38 (2019) 1561e1569mentioning
confidence: 84%
“…Previous observations have suggested that endotoxins from non-commensal bacteria may affect adipocytokine levels secondary to translocation induction of several intestinal microbial antigens into the circulation, creating an altered adipokine profile and intestinal dysbiosis [34]. Certain probiotics, specifically lactic acid bacteria strains, have demonstrated in vitro that they can differentially modulate adipokine expression and the inflammatory response [35]. It is noteworthy that 6 of the 8 probiotic strains used in this study belong to the lactic acid bacteria class.…”
Section: S Sabico Et Al / Clinical Nutrition 38 (2019) 1561e1569mentioning
confidence: 84%
“…of TNF-α, IL-6, IL-10 and MCP-1 in adipocytes. Lactococcus lactis CRL1434 strain increases TNF-α, MCP-1, and IL-10 expression in comparison to other strains, while the Lactobacillus plantarum CRL350 strain induced higher levels of IL-6 (Fabersani et al, 2017). IL-6 is secreted by adipocytes primarily in sites that present with acute or chronic inflammation, such as by the visceral adipose tissue (Castoldi, De Souza, Saraiva Câmara, & Moraes-Vieira, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Different probiotic strains of Lactobacillus genera acquire significant and widely acknowledged immunomodulatory properties and health-promoting [35,138]. The approaches leading to the efficient targetness engages the natural ways which do not cause any side effects and assist the body to uphold the immune homeostasis such as the use of probiotics are the ways forward.…”
Section: Discussionmentioning
confidence: 99%
“…The market size of probiotics has to the highest degree increased consumer anxiety concerning health-promoting effect of nutraceuticals [38,138,151].…”
Section: Discussionmentioning
confidence: 99%